Power Relations among Caregivers, Ustaz, and Students as Well as the Formation of Social Compliance in Islamic Boarding Schools - Fina Afnan Feyza; Muh. Hanif (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2026)
This article examines the power relations among caregivers, ustaz, and students and how these relationships shape social compliance in Islamic boarding schools. From the perspective of the sociology of educational institutions, this study argues that social obedience in boarding schools is not formed naturally, but through networks of power relations legitimized by religious authority, boarding school traditions, and daily supervision systems. Using a qualitative case study approach at the An-Najah Student Boarding School, data were collected through participatory observation, in-depth interviews, and institutional documentation. The results reveal three main mechanisms for fostering social compliance: first, interpreting orders as an integral part of scientific ethics; second, seniority structures and management systems that strengthen social control; third, religious worship and learning routines used as a medium for collective obedience training. This study concludes that social compliance in boarding schools grows from an understanding of values and mutual agreement, rather than merely from coercion, making boarding schools places for students' character formation and social identity.